Ephebophilia Suffered by the Main Character - Dina Amelia; Febri Diantika Dintasi (Universitas Teknokrat Indonesia, 2017)
Lolita was written by a Russian writer Vladirmir Nabokov in the twentieth century. Humbert, the male character in the story, was considered to be an ephebophile since he was attracted to girls in their adolescences. The author wrote about the character’s sexual orientation which led to his downfall. Psychological approach and ephebophilia theory applied in this research in order to reveal the description of Humbert’s sexual orientation. Meanwhile, the data for this research were taken from the dialogues and narrations in Lolita novel. As it is a library research, the writers took the seconday data needed from books, journals, articles, and internet sites to analyze the issue. Hence, in conducting the research, descriptive qualitative method was applied to elaborate the data concerning to the research queation. After applying those techniques and analyzing data, the writers drew several conclusions. Ephebophilia was not only focus on the sexual encounters, but also on the sexual attraction. In this case, the construction of ephebohilia in the main character was influenced by his unforgettable sexual encounter with his teenage lover. Therefore, Humbert became fixated to much younger women and he could not escape from his burning desire. His sexual encountered with his teenage lover had also influenced the way he saw the young girls. He often fantasized and sexually attracted to them. Overall, throughout the story, Humbert had suffered due to his sexual orientation. Nabokov was able to present the male character’s dilema and grief who desperately needed help.